2019
DOI: 10.1177/0003319719830495
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cell Parameters and Predicting Coronary In-Stent Restenosis

Abstract: Major advances in coronary interventional techniques and pharmacotherapy as well as the use of drug-eluting stents (DESs) have considerably reduced the risk of in-stent restenosis (ISR). However, ISR remains a major clinical challenge. Inflammation and platelet activation are important processes that underlie the pathophysiology of ISR. Parameters related to blood cells, entailing both cell count and morphology, are useful markers of the inflammatory response and platelet activation in clinical practice. Recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 99 publications
2
23
0
1
Order By: Relevance
“…The rate of NSTE myocardial infarction (NSTEMI) was higher in the ISR group than in the non-ISR group (50.0% vs 16.8%, p=0.001). The rate of presence of a bifurcation lesion was higher and time between the two CAG scans was longer in the ISR group than in the non-ISR group (37.5% vs 15.3%, p=0.019; 27.5 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] vs 23.0, [16][17][18][19][20][21][22][23][24][25][32][33][34][35] p=0.043, respectively). Angiographic and PCI results, including the rate of calcification lesion, lesion type according to the AHA classification, generation of the implanted stents, the total stent length, maximum stent diameter, and post-dilatation indication, were similar in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…The rate of NSTE myocardial infarction (NSTEMI) was higher in the ISR group than in the non-ISR group (50.0% vs 16.8%, p=0.001). The rate of presence of a bifurcation lesion was higher and time between the two CAG scans was longer in the ISR group than in the non-ISR group (37.5% vs 15.3%, p=0.019; 27.5 [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] vs 23.0, [16][17][18][19][20][21][22][23][24][25][32][33][34][35] p=0.043, respectively). Angiographic and PCI results, including the rate of calcification lesion, lesion type according to the AHA classification, generation of the implanted stents, the total stent length, maximum stent diameter, and post-dilatation indication, were similar in both groups.…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reviewed that several parameters of blood cells, including the NLR, platelet-to-lymphocyte ratio (PLR), red blood cell distribution width (RDW), mean platelet volume (MPV), and platelet distribution width (PDW), [ 4 ] can be used as risk predictors for DES-ISR in different clinical settings, while NLR may be the best predictor of DES-ISR among them. [ 5 ] However, our study showed that there were no significant differences in pre-procedural levels of PLR, RDW, MPV, and PDW between ISR group and non-ISR group. Different study populations and small number of samples may explain this discrepancy.…”
mentioning
confidence: 53%
“…Многими авторами рестеноз стентированного сегмента рассматривается как следствие затянувшейся воспалительной реакции в стентированном участке. Показана связь между вероятностью рестеноза и содержанием в крови пациентов различных воспалительных маркеров (вч-СРБ, моноцитарный хемотаксический белок-1, миелопероксидаза, кардиотропин-1, интерлейкин-6, показатели активности тромбоцитов) [28][29][30][31]. Согласно результатам исследований [32][33][34], повышенный уровень вч-СРБ в пред-, пери-и в постпроцедурном периодах является фактором риска рестеноза в стенте.…”
Section: Discussionunclassified